Evaluation of the MRSA Sensitivity to Essential Oils Obtained from four Algerian Medicinal Plants - KHADIR Abdelmounaïm, BENDAHOU Mourad, BENBELAID Fethi, BELLAHCENE Chafika, ABDELOUAHID Djamel-Eddine, MUSEILI Alin, PAOLLINI Julien, DESJOBER Jymy, COSTA Jean (Journal of Applied Pharmaceutical Science, 2013)
In this work, we evaluated the anti-MRSA activity of essential oils obtained from four Algerian medicinal plants which are: Ammoides verticillata, Origanum vulgare subsp. glandulosum, Lavandula multifida, and Thymus munbyanus subsp. ciliatus. The anti-MRSA activity was evaluated by the technique of agar diffusion and determination of MICs. We also studied the kinetics of destruction of these oils against MRSA strain ATCC 43300. The four essential oils showed a good anti-MRSA activity. Oils with the highest activity are; Origanum vulgare subsp. glandulosum, Thymus munbyanus subsp. ciliatus, Lavandula multifida and Ammoides verticillata respectively. The kinetics of destruction of all essential oils against MRSA ATCC 43300 strain is dependent on concentration. The Concentration 1% allows a total destruction; while the concentration 0.5% was bactericidal only with Origanum vulgare, whereas the concentration 0.25% and 0.125% have had a low destruction respectively. We concluded that the essential oils can be used as an anti-MRSA.
Keywords: MRSA, essential oils, kinetics of destruction, bacte